Making Known the Real: An Exploration of Academic Advising Practices in a South African Higher Education Context (Journal of Student Affairs in Africa, 2012)
This is the first in a series of papers that emanate from the author’s doctoral research. This research explores academic advising as a profession and academic advisors as practitioners in the South African Higher Education sector; it focuses on advising within the Faculty of Commerce, Law and Management (FCLM) at a research-intensive public university in South Africa. During the period of investigation, academic advising engagements between students and the author were logged, thus forming a baseline dataset for the doctoral study. In phase one of the data analysis, baseline data were coded and clustered into overarching and subsidiary categories. The baseline dataset consists of 34 subsidiary categories, which form part of seven overarching categories; it contains 2240 entries based on 1023 consultations with 614 individual students during the three-year period under investigation. Using Archer’s (1995, 2000, 2005) notions about Social Realism as a theoretical framework, the author critically scrutinises the complex nature of the work that academic advisors do in a layered analysis of the baseline data. The author posits that it is through these layers of interpretation that one moves from the layer of the Empirical (experiences), through the layer of the Actual (events), to what Archer calls “the Real”, that is, the layer of mechanisms or underlying driving forces that brings about what happens in the layers of the Empirical and the Actual. This paper focuses specifically on the role of the academic advisor; it postulates inferential observations about academic advising by using the baseline dataset as a way in, while keeping the academic advisor central to the discussion.
Keywords: academic advising; higher education; holistic supports; social realism; South Africa; student access; student support; structure; culture; agency